The mystery of prayer :the ascension of the wayfarers and the prayer of the gnostics = Sirr al-ṣalāh : miʻrāj al-sālikīn wa-ṣalāt al-ʻārifīn - Khomeini, Ruhollah. (The Modern Shīʿah Library, 2015)
Sayyid Amjad Hussain Shah Naqavi's introduction and annotated scholarly translation of Ayatollah Khomeini's The Mystery of Prayer brings to light a rarely studied dimension of an author better known for his revolutionary politics. Writing forty years before the Islamic revolution, Khomeini shows a formidable level of insight into the spiritual aspects of Islamic prayer. Through discussions on topics such as spiritual purity, the presence of the heart before God, and the stations of the spiritual wayfarer, Khomeini elucidates upon the nature of reality as the countenance of the divine. Drawing upon scriptural sources and the Shīʿah intellectual and mystical tradition, the subtlety of the work has led to it being appreciated as one of Khomeini's most original works in the field of gnosis.